The orderly splicing of the first three leaders of the adenovirus-2 major late transcript. - Keohavong, P (1982)
A strategy based on the hybridization of labeled nucleoplasmic RNA to a short cloned cDNA probe was devised to study the ligation of the three first leader sequences (Le1, Le2, Le3) of the major late adenovirus-2 transcript. The hybridized RNA was subsequently fractionated by electrophoresis and identified with the aid of restriction fragments of the DNA probe. The ligations were shown to occur stepwise and in an orderly fashion. Le1 and Le2 were first ligated without detectable lag time. The tripartite leader was formed after a lag time of 10-15 min probably due, for a large part, to the stepwise excision of the intervening sequence between Le2 and Le3. The possible processing intermediate Le2-Le3 was not detected.